2014
DOI: 10.1530/eje-13-0754
|View full text |Cite
|
Sign up to set email alerts
|

Is diabetes in Cushing's syndrome only a consequence of hypercortisolism?

Abstract: Objective: Diabetes mellitus (DM) is one of the most frequent complications of Cushing's syndrome (CS). The aim of this study was to define the changes in insulin sensitivity and/or secretion in relation to glucose tolerance categories in newly diagnosed CS patients. Design: Cross-sectional study on 140 patients with CS. Methods: A total of 113 women (80 with pituitary disease and 33 with adrenal disease, aged 41.7G15.7 years) and 27 men (19 with pituitary disease and eight with adrenal disease, aged 38.1G20.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 39 publications
3
60
0
2
Order By: Relevance
“…Unfortunately, concordance with LNSC has not been performed. However, previous studies have reported a significant correlation between UFC and LNSC [39][40][41], showing even a better performance of LNSC compared to UFC in the diagnosis of Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 83%
“…Unfortunately, concordance with LNSC has not been performed. However, previous studies have reported a significant correlation between UFC and LNSC [39][40][41], showing even a better performance of LNSC compared to UFC in the diagnosis of Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 83%
“…No significant gender differences have been reported (6). Diabetic CS patients have been found to be older than normoglycaemic or prediabetic CS patients (7). Nevertheless, reported prevalence could be underestimated because available data were largely based on the measurement of fasting blood glucose.…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 98%
“…Diabetes mellitus in Cushing's syndrome is characterized by the inability of β-cells to compensate for insulin resistance [6]. Since diabetes mellitus causes various health problems such as cardiovascular disease, renal disease and neuropathies, the screening for diabetes in patients with Cushing's syndrome is important to improve their prognosis.…”
mentioning
confidence: 99%